EGF Enhances Oligodendrogenesis from Glial Progenitor Cells - Yang, Junlin; Cheng, Xuejun; Qi, Jiajun; Xie, Binghua; Zhao, Xiaofeng; Zheng, Kang; Zhang, Zunyi; Qiu, Mengsheng (Frontiers in Molecular Neuroscience, 2017)
Emerging evidence indicates that epidermal growth factor (EGF) signaling plays a positive role in myelin development and repair, but little is known about its biological effects on the early generation and differentiation of oligodendrocyte lineage cells. In this study, we investigated the role of EGF in early oligodendrocyte development with isolated glial restricted precursor (GRP) cells. It was found that EGF collaborated with Platelet Derived Growth Factor-AA (PDGFaa) to promote the survival and self-renewal of GRP cells, but predisposed GRP cells to develop into O4- early-stage oligodendrocyte precursor cells (OPCs) in the absence of or PDGFaa. In OPCs, EGF synergized with PDGFaa to maintain their O4 negative antigenic phenotype. Upon PDGFaa withdrawal, EGF promoted the terminal differentiation of OPCs by reducing apoptosis and increasing the number of mature oligodendrocytes. Together, these data revealed that EGF is an important mitogen to enhance oligodendroglial development.